Are You Satisfied With Shopee? A Study of Customer Satisfaction Towards Shopee - Kee, Daisy Mui Hung; Wawi, Mohamad Haniff Hilman; Zohri, Mohd Hidayat Ahmad; Mok, Hui Xin; Mok, Man Nee; Rafif, Muhammad Ilham; Lutfiani, Lina Silvia; Hafizh, Ubaidillah; Priyambodo, Haryo Gilar (AIBPM Publisher, 2023)
Shopee is an e-commerce business that was launched in 2015. As of 2021, Shopee is regarded as Southeast Asia's largest e-commerce platform. In just a few years, Shopee has leveraged its strong competitive advantage to aggressively expand its presence in Southeast Asia and achieve a leading position in the highly competitive e-commerce space. Regarding total time spent in the app and monthly active users, the Shopee app is constantly ranked as the top app in the shopping category in Southeast Asia. This study seeks to ascertain the factors that affect customer satisfaction towards Shopee. Data were collected using an online survey. A total of two hundred respondents participated in the survey through Google Forms. The results revealed that most customers are satisfied with Shopee from the aspects of perceived usefulness, perceived benefits, perceived convenience as well as perceived trust. For instance, the findings of this study suggest that the factors such as perceived benefits and perceived trust have the most significant influence on customer satisfaction with Shopee. This study has brought valuable feedback and insights from Shopee's customers. It also enables Shopee to identify shortcomings and provide better services to customers in the future to improve customer satisfaction.